2019
DOI: 10.1002/jcp.29352
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic eight‐lncRNA expression signature in predicting recurrence of ER‐positive breast cancer receiving endocrine therapy

Abstract: Long noncoding RNAs (lncRNAs) have the main role in the tumorigenesis of breast cancer. In the present study, lncRNA expression profiling was collected to identify a lncRNA expression signature from the Gene Expression Omnibus database. An eight-lncRNA signature was established to predict the survival of patients with estrogen receptor (ER)-positive breast cancer receiving endocrine therapy. Patients were separated into a low-risk group and a high-risk group based on this signature. Patients in high-risk group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…17 In 2020, Tang et al also manufactured a signature consisting of 8 lncRNAs for ER-BC-positive analysis, which could predict survival in patients receiving endocrine therapy. 18 Thus, it could conclude that ncRNAs, represented by lncRNAs, had the immeasurable potential of prognostic value and ability in BC. More importantly, Ye et al constructed a prognostic signature composed of 7 pyroptosis-related mRNAs in 2021.…”
mentioning
confidence: 99%
“…17 In 2020, Tang et al also manufactured a signature consisting of 8 lncRNAs for ER-BC-positive analysis, which could predict survival in patients receiving endocrine therapy. 18 Thus, it could conclude that ncRNAs, represented by lncRNAs, had the immeasurable potential of prognostic value and ability in BC. More importantly, Ye et al constructed a prognostic signature composed of 7 pyroptosis-related mRNAs in 2021.…”
mentioning
confidence: 99%
“…For instance, Wang et al identified an 11-lncRNAs-based signature that could predict longer RSF in ER-positive BC patients treated with tamoxifen [204]. On the other hand, Tang et al developed a lncRNA signature indicative of recurrence in ER-positive BC patients receiving endocrine therapy [254]. Jiang and colleagues also discovered an mRNA-lncRNA signature able to subdivide TNBC patients into groups with high or low risk of relapse.…”
Section: Ncrnas and Their Predictive Value In Bcmentioning
confidence: 99%
“…Development of omics technology has contributed to the diagnosis and treatment of cancers in a systematic approach [ 21 ]. Recently, a method that commonly utilized microarray data for the express profiling of lncRNAs has been well-constructed, which might advance the therapeutic measures for human cancers [ 22 , 23 ]. A unique prognostic nomogram has been established based on the five-lncRNAs signature in clear cell renal cell carcinoma [ 24 ].…”
Section: Introductionmentioning
confidence: 99%